Keracunan Makanan - Raya Marcela; Karfika Suci Ramadhani; Muhammad Fiqri Alwi; Usiono Usiono (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Food poisoning is a health problem that often occurs in various parts of the world. The cause can come from bacteria, viruses, fungi, or contaminated chemicals in food. The aim of this research is to identify the causes of food poisoning and its impact on human health. The method used in this research is a qualitative method using descriptive methods. The observations made by the author in this research were direct observation or observation of the field by making direct observations with Durin Simbelang A. The researcher also conducted interviews with PMR sources, namely 4 sources. This research was structured based on questions asked by researchers to data sources through interview techniques. Based on the results of the research conducted, researchers obtained data namely: 1. There are those who have experienced food poisoning and there are those who have never experienced food poisoning. 2. There are several symptoms if you experience food poisoning. 3. There are ways to deal with food poisoning.